Α‐ketoglutarate delays age‐related fertility decline in mammals. Issue 2 (15th January 2021) - Zhang, Zhenzhen; He, Changjiu; Gao, Yu; Zhang, Lu; Song, Yukun; Zhu, Tianqi; Zhu, Kuanfeng; Lv, Dongying; Wang, Jing; Tian, Xiuzhi; Ma, Teng; Ji, Pengyun; et al.
Abstract: The fecundity reduction with aging is referred as the reproductive aging which comes earlier than that of chronological aging. Since humans have postponed their childbearing age, to prolong the reproductive age becomes urgent agenda for reproductive biologists. In the current study, we examined the potential associations of α‐ketoglutarate (α‐KG) and reproductive aging in mammals including mice, swine, and humans. There is a clear tendency of reduced α‐KG level with aging in the follicle fluids of human. To explore the mechanisms, mice were selected as the convenient animal model. It is observed that a long term of α‐KG administration preserves the ovarian function, the quality and quantity of oocytes as well as the telomere maintaining system in mice. α‐KG suppresses ATP synthase and alterations of the energy metabolism trigger the nutritional sensors to down‐regulate mTOR pathway. These events not only benefit the general aging process but also maintain ovarian function and delay the reproductive decline. Considering the safety of the α‐KG as a naturally occurring molecule in energy metabolism, its utility in reproduction of large mammals including humans deserves further investigation. Abstract : Long term of α‐ketoglutarate (α‐KG) administration preserves the ovarian function, the quality and quantity of oocytes as well as telomere maintaining system in mice. α‐KG suppresses ATP synthase and alterations of the energy metabolism trigger the nutritional sensors to down‐regulate mTOR pathway. These events not only benefit the general aging process but also maintain ovarian function and delay the reproductive decline.